microRNA-mediated integration of haemodynamics and Vegf signaling during angiogenesis - Nicoli, Stefania (2010)
Within the circulatory system, blood flow regulates vascular remodeling1, stimulates blood stem cell formation2, and plays a role in the pathology of vascular disease3. During vertebrate embryogenesis, vascular patterning is initially guided by conserved genetic pathways that act prior to circulation4. Subsequently, endothelial cells must incorporate the mechanosensory stimulus of blood flow with these early signals to shape the embryonic vascular system4. However, few details are known about how these signals are integrated during development. To investigate this process, we focused on the aortic arch (AA) blood vessels, which are known to remodel in response to blood flow1. By using 2-photon imaging of live zebrafish embryos, we observe that flow is essential for angiogenesis during AA development. We further find that angiogenic sprouting of AA vessels requires a flow-induced genetic pathway in which the mechano-sensitive zinc finger transcription factor klf2a5-7 induces expression of an endothelial-specific microRNA, mir-126, to activate Vegf signaling. Taken together, our work describes a novel genetic mechanism in which a microRNA facilitates integration of a physiological stimulus with growth factor signaling in endothelial cells to guide angiogenesis.